The Prevalence and Diagnostic Ratio of Familial Hypercholesterolemia (FH) and Proportion of Acute Coronary Syndrome in Japanese FH Patients in a Healthcare Record Database Study - Tamio Teramoto; Tomohiro Sawa; Satoshi Iimuro; Hyoe Inomata; Takashi Koshimizu; Iori Sakakibara; Katsutoshi Hiramatsu (Hindawi-Wiley, 2020)
Background. Familial hypercholesterolemia (FH) is a genetic disorder characterized by high levels of low-density lipoprotein cholesterol (LDL-C). Because of underdiagnosis, acute coronary syndrome (ACS) is often the first clinical manifestation of FH. In Japan, there are few reports on the prevalence and diagnostic ratios of FH and the proportion of ACS among FH patients in clinical settings. Methods. This retrospective, observational study used anonymized data from electronic healthcare databases between April 2001 and March 2015 of patients who had ≥2 LDL-C measurements recorded after April 2009. The index date was defined as the date of the first LDL-C measurement after April 2009. The primary endpoint was the prevalence of definite or suspected FH; secondary endpoints included the proportion of FH patients hospitalized for ACS, the proportion of patients using lipid-lowering drugs (LLDs), and LDL-C levels. Results. Of the 187,781 patients screened, 1547 had definite or suspected FH (0.8%) based on data from the entire period; 832 patients with definite (n=299, 0.16%) or suspected FH (n=533, 0.28%) before the index date were identified in the main analysis cohort. LLDs were used in 214 definite FH patients (71.6%) and 137 suspected FH patients (25.7%). Among definite or suspected FH patients with ACS (n=84) and without ACS (n=748), 32.1% and 30.1% with definite FH and 3.2% and 2.4% with suspected FH had LDL-C levels<2.6 mmol/L (<100 mg/dL), respectively. Sixty patients (7.2%) were hospitalized due to ACS at the index date. Conclusions. The prevalence of FH in this Japanese cohort of patients with ≥2 LDL-C measurements at hospitals was 0.8%, which is higher than that currently reported in epidemiological studies (0.2-0.5%). Patients with suspected FH, with or without ACS, had poorly controlled LDL-C levels and were undertreated. The proportion of FH patients who were hospitalized due to ACS was 7.2%.